Anatomical correlates of quality of life: Evidence from voxel‐based morphometry. Issue 5 (14th May 2013) - Takeuchi, Hikaru; Taki, Yasuyuki; Nouchi, Rui; Hashizume, Hiroshi; Sassa, Yuko; Sekiguchi, Atsushi; Kotozaki, Yuka; Nakagawa, Seishu; Nagase, Tomomi; Miyauchi, Carlos Makoto; Kawashima, Ryuta
<x xml:space="preserve">Abstract</x> Quality of life (QOL) has been defined in many ways, and these definitions usually emphasize happiness and satisfaction with life. Health‐related problems are known to cause lower QOL. However, the neural mechanisms underlying individual differences in QOL measured by questionnaire (QOLMQ) in young healthy subjects are unknown. QOL is essential to our well‐being, and investigation of the neural mechanisms underlying QOL in uncompromised subjects is obviously of great scientific and social interest. We used voxel‐based morphometry to investigate the association between regional gray matter volume (rGMV) and QOLMQ across the brain in healthy young adults (age, 21.4 ± 1.8 years) men (n = 88) and women (n = 68) in humans. We found significant negative relationships between QOLMQ and rGMV in a region in the left rostrolateral prefrontal cortex and regions in the dorsal part of the anterior cingulate gyrus and contingent cingulate regions. These findings show that structural variations in regions associated with processing of negative emotions such as fear and anger as well as those associated with evaluation of internally generated information are associated with QOLMQ. These findings suggest that these processes might be related to QOLMQ in healthy young adults. Hum Brain Mapp 35:1834–1846, 2014. © 2013 Wiley Periodicals, Inc.